2015
DOI: 10.1002/2015jb012272
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami inundation from heterogeneous earthquake slip distributions: Evaluation of synthetic source models

Abstract: This study investigates whether eight different synthetic finite fault models (SFFM) can simulate stochastic earthquake‐tsunami with similar statistical properties to “real” earthquake‐tsunami events, where the latter are represented using heterogeneous slip distributions from 66 Finite Fault Inversions (FFI) for oceanic subduction interface earthquakes. A new method is derived to estimate SFFM parameters from FFI, and predictive relations between the earthquake moment magnitude and the SFFM corner wave number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 80 publications
0
38
0
Order By: Relevance
“…Probabilistic tsunami hazard analysis (PTHA) probably began with the seminal papers of Lin and Tung (1982) and Rikitake and Aida (1988). Uncertainty quantification is one of the main goals of PTHA, and progressively more refined uncertainty treatment was achieved following the 2004 Indian Ocean tsunami (e.g., Geist and Parsons, 2006;Burbidge et al, 2008;González et al, 2009;Horspool et al, 2014;Hoechner et al, 2016;Selva et al, 2016;Davies et al, 2017;Grezio et al, 2017;Power et al, 2017). PTHA is becoming the established good practice for managing risk assessment and risk mitigation measures (Chock et al, 2016;Løvholt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Probabilistic tsunami hazard analysis (PTHA) probably began with the seminal papers of Lin and Tung (1982) and Rikitake and Aida (1988). Uncertainty quantification is one of the main goals of PTHA, and progressively more refined uncertainty treatment was achieved following the 2004 Indian Ocean tsunami (e.g., Geist and Parsons, 2006;Burbidge et al, 2008;González et al, 2009;Horspool et al, 2014;Hoechner et al, 2016;Selva et al, 2016;Davies et al, 2017;Grezio et al, 2017;Power et al, 2017). PTHA is becoming the established good practice for managing risk assessment and risk mitigation measures (Chock et al, 2016;Løvholt et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This work was continued in Geist (2012) who showed that far-field amplitude scaled with scalar seismic moment but with significant uncertainty in the correlation. Other studies, such as Davies et al (2015), McCloskey et al (2007McCloskey et al ( , 2008, Løvholt et al (2012) or Goda et al (2014), have investigated the effect of non-uniform slip on the nearshore maximum tsunami height or on the maximum inundation height. However, these studies have generally focused on one particular location and thus on a limited range of distances and azimuths.…”
Section: Burbidge Et Al: Tsunami Uncertaintymentioning
confidence: 99%
“…For instance, scaling relationships that evaluate the width and length of a fault plane as a function of moment magnitude can be used to determine the geometry of an earthquake rupture for a given scenario. Moreover, randomness and heterogeneity of spatial earthquake slip distribution, which have major influence on tsunami hazard assessment [Geist, 2002;Løvholt et al, 2012;Goda et al, 2014Goda et al, , 2015Davies et al, 2015], can be characterized by wavenumber spectra [Mai and Beroza, 2002;Lavallée et al, 2006]. Possible realizations of constrained random slip fields are normally generated using spectral synthesis methods and integrated into probabilistic tsunami hazard and risk assessment [Goda et al, 2014Fukutani et al, 2015;Goda and Abilova, 2016].…”
Section: Introductionmentioning
confidence: 99%